Heberden's Nodes and Knee Osteoarthritis–Related Osseous Structural Damage: Exploratory Study From the Osteoarthritis Initiative - Haj-Mirzaian, Arya; Mohajer, Bahram; Guermazi, Ali; Shakoor, Delaram; Haugen, Ida K.; Roemer, Frank; Demehri, Shadpour (Arthritis and Rheumatology, 2019)
Objective: To explore whether Heberden's nodes (HNs) could predict magnetic resonance imaging (MRI)–based knee osteoarthritis (OA)–related osseous structural progression. Methods: Five hundred seventy-five subjects from the Foundation for the National Institutes of Health project underwent clinical examination to evaluate HNs at baseline and knee MRI at baseline and 24 months. The MRI was read according to the semiquantitative MRI OA Knee Score and quantitative periarticular bone morphology measures. Adjusted linear/logistic regression models were implemented to assess the association between the presence of HNs at baseline examination and worsening of MRI-defined osseous structural damage, and odds ratios (ORs) with 95% confidence intervals (95% CIs) were calculated. Results: Comparing patients with HNs (n = 395) and patients without HNs (n = 180), more periarticular bone area expansion in the knee joint was seen in the patients with HNs over 24 months (adjusted OR [OR adj ] 1.39 [95% CI 1.06, 1.83], corrected P [P corr ] = 0.019), especially in the medial femur (OR adj 1.49 [95% CI 1.05, 2.13], P corr = 0.026) and lateral femur (OR adj 2.51 [95% CI 1.58, 3.97], P corr < 0.001), femoral notch (OR adj 1.37 [95% CI 1.02, 1.84], P corr = 0.04), and lateral trochlea (OR adj 1.44 [95% CI 1.08, 1.9], P corr = 0.012). However, a trend toward less osteophyte worsening was seen in patients with HNs in the whole knee joint (OR adj 0.63 [95% CI 0.40, 1.02], P corr = 0.058), particularly in the femur region (OR adj 0.54 [95% CI 0.31, 0.95], P corr = 0.03), compared to patients without HNs. Conclusion: The presence of HNs was associated with increased MRI-based periarticular bone area expansion, but less osteophyte worsening over 24 months in the knee joint, especially in the femoral region.
CRIS-Team Scopus Importer:2019-05-02